Direct nose to brain delivery of small molecules: critical analysis of data from a standardized in vivo screening model in rats - Deborah Dhuyvetter; Fetene Tekle; Maxim Nazarov; Rob J. Vreeken; Herman Borghys; Frederik Rombouts; Ilse Lenaerts; Astrid Bottelbergs (Taylor & Francis Group, 2020)
The blood-brain barrier (BBB) is often a limiting factor for getting drugs in the brain. Bypassing the BBB by intranasal (IN), or also called nose to brain (NTB), route is an interesting and frequently investigated concept for brain drug delivery. However, despite the body of evidence for IN drug delivery in literature over the last decades, reproducibility and interpretation of animal data remain challenging. The objective of this project was to assess the feasibility and value of a standardized IN screening model in rats for the evaluation of direct brain delivery. A chemically diverse set of commercial and internal small molecules were tested in the in vivo model with different doses and/or formulations. Data were analyzed using different ways of ratio calculations: blood concentration at time of sacrifice, total exposure in blood (area under the curve, AUC) and the brain or olfactory bulb concentrations. The IN route was compared to another parenteral route to decide if there is potential direct brain transport. The results show that blood and tissue concentrations and ratios are highly variable and not always reproducible. Potential direct brain delivery was concluded for some compounds, however, sometimes depending on the analysis: using blood levels at sacrifice or AUC could lead to different conclusions. We conclude that a screening model for the evaluation of direct brain transport of small molecules is very difficult to achieve and a conclusion based on a limited number of animals with this variability is questionable.